A Study on the Effect of Multistage Toolpath in Fabricating a Customized Cranial Implant in Incremental Sheet Metal Forming - Fahad, Mohamed I.; Shammari, Ahmed Z. M.; Nasir, Ramdziah binti Md (Al-Khwarizmi Engineering Journal, 2023)
Incremental sheet forming (ISF) process offers a high degree of flexibility in the manufacturing of different sheet parts, which makes it an ideal candidate for prototype parts as well as efficient at fabricating various customized products at low production costs compared to traditionally used processes. However, parts produced in this process exhibit notable geometrical inaccuracy and considerable thickness reduction. In this paper, the single point incremental sheet forming variant of the process has been implemented to manufacture a highly customized cranial implant starting from the computed tomography (CT) scan data of the patient’s anatomy. A methodology, from the modeling to the realization of the implant, is presented and discussed. The primary aim of the research was to analyze and study the effect of the multistage toolpath strategy compared to the traditional single-stage toolpath in terms of geometrical accuracy and thickness distribution. The final results show that the part formed in the multistage toolpath strategy exhibited a more uniform thickness distribution compared to the single-stage approach. Regarding the geometrical accuracy, the deviation analysis between the nominal and actual data has revealed that the multistage forming has significantly enhanced the final geometrical accuracy of the formed part.